Comparative study on direct shear behavior of manufactured and recycled shredded tyre steel fiber reinforced self-consolidating concrete. (May 2020) - Simalti, Ashish; Singh, A.P.
Abstract: This article presents the experimental study on the shear behavior of self-consolidating concrete (SCC) reinforced with recycled steel fibers (RSF), obtained from scrap tyres and manufactured steel fibers (MSF). A total of seven mixes were prepared viz SCC with no fiber as control mix, SCC with the inclusion of MSF with 0.5%, 1.0% and 1.5% volume fraction and RSF with varying volume fractions of 0.5%, 1%, and 1.5%. To increase the workability and viscosity of SCC, fly ash and silica fume (SF) was added in an appropriate proportion. The use of these materials promotes the sustainable use of waste. It was observed that the shear strength of SCC mix with RSF improved as compared to that of plain SCC but decreased as compared to SCC with MSF. A statistical model based on experimental data has been developed for predicting the shear strength of SCC containing MSF and RSF. An attempt has been made to predict the shear strength of mixes used in studies available in the literature. Highlights: Feasibility of using RSF in SCC was done. To evaluate the effectiveness of RSF in shear, a comparison was done with MSF and control mix. RSF lesser effective in shear strength than MSF, but an effective solution for the economic and environmental aspect. A mathematical model is given for shear strength and compared with the available model in the literature.